Integrasi Metode Servqual dan Quality Filter Mapping (QFM) Dalam Upaya Peningkatan Kualitas Produk Plywood pada PT XYZ - Yasin, Muhamad; Foci, Nia Arfina; Munanda, M Arif; Putra, Rama Dani Eka; Fitri, Tessa Zulenia; Brillianio, Nindya Nuanda Ardha (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT XYZ still produces many product defects that exceed the specified permissible limits. This company has a product defect margin of 2.50% of total production. The purpose of this study is to improve product quality by facing fierce competition and become a theoretical reference in suppressing product failures and information to determine its importance using servqual and QFM. Servqual is a service quality measurement method developed by Parasuraman, et al. QFM is a quality management tool to map and identify critical points in the service process that affect quality. The implementation of PDCA in the company needs to be improved again and the implementation of 5R in the company needs to be improved. The largest waste in the Birch 4.6 mm product is Repair with a Press Mark defect type of 0.47% and in the Birch 18 mm product, the highest Fail Reject Defect is a bubble of 3.57%.